2017
DOI: 10.1155/2017/3823621
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Cement Hydration with NS@PCE Core-Shell Nanoparticles

Abstract: It is generally accepted that fine particles could accelerate cement hydration process, or, more specifically, this accelerating effect can be attributed to additional surface area introduced by fine particles. In addition to this view, the surface state of fine particles is also an important factor, especially for nanoparticles. In the previous study, a series of nano-SiO 2 -polycarboxylate superplasticizer core-shell nanoparticles (NS@PCE) were synthesized, which have a similar particle size distribution but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition, the mineral additions provide additional surfaces promoting the chemical reactions: this catalytic effect, called the filler effect, partly attenuates the dilution effect, that is the replacement of the cement by less reactive materials. The filler effect could also be described as a seeding effect as nanoparticles are considered [26], involving nucleation as its physical origin. Nevertheless, the dependence to the interparticle distance also points shearing mechanisms as another plausible physical origin [27] for quartz fillers, fly ashes, slag and limestone fillers.…”
Section: Modelling Of Cement Hydration In Briefmentioning
confidence: 99%
“…In addition, the mineral additions provide additional surfaces promoting the chemical reactions: this catalytic effect, called the filler effect, partly attenuates the dilution effect, that is the replacement of the cement by less reactive materials. The filler effect could also be described as a seeding effect as nanoparticles are considered [26], involving nucleation as its physical origin. Nevertheless, the dependence to the interparticle distance also points shearing mechanisms as another plausible physical origin [27] for quartz fillers, fly ashes, slag and limestone fillers.…”
Section: Modelling Of Cement Hydration In Briefmentioning
confidence: 99%
“…Indeed, the lifetime curves of the samples demonstrate a complicated shape (Figures 6(a) and 6(b)). It can be suggested that there are several physical processes which can be responsible for luminescence quenching [11]. Some of these processes can be temperature dependent.…”
Section: Luminescence Lifetime Ermometrymentioning
confidence: 99%
“…Among different methods of nanothermometry such as using nanoscale thermocouples [3] and coulomb blockade nanothermometers [4], the luminescent nanothermometers hold a special place because of its high spatial and temporal resolution, accuracy, and contactlessness [1,[4][5][6][7]. Rareearth-doped nanomaterials hold a special role in luminescent nanothermometry among other luminescent nanomaterials because of their excellent photostability [8,9], long luminescent lifetimes [10,11], sharp emission bands, high brightness [12,13], high melting point, promising magnetic properties [14,15], and good resistance to thermal and chemical attacks [16,17]. More importantly, rare earth ions doped into fluoride nanoparticles demonstrate even better optical properties in comparison with some counterparts [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…erefore, a suitable surface agent is important for cementitious materials surface modification. Polyacrylic acid (PAA) with short branch chain of carboxyl groups is a common surface modification agent [39][40][41]. e hydrophilic groups of PAA can isolate nanoparticles by its charge repulsion and the steric hindrance after grafted on the particle surface and form a hydrophilic layer around the particle.…”
Section: Introductionmentioning
confidence: 99%